Thin-capitalization rules and company responses experience from German legislation - Alfons J. Weichenrieder; Helen Windischbauer (Center for Economic Studies and ifo Institute (CESifo), 2008)
By granting intracompany loans to their foreign affiliates, multinational firms may reduce their tax liability abroad. Many countries have legislated thin-capitalization rules (TCRs) that limit the allowable levels of intracompany loans or restrict interest deductibility if certain thresholds are crossed. This paper empirically analyzes the effect of the German TCR on corporate policy. We find that tightening the regulations in 2001 had some limiting effect on leverage. Foreign affiliates reacted by reducing intracompany loans and increasing equity, with no significant evidence of reduced real investment. A possible reason for the limited impact of the TCR was that multinational firms had the option to work around the regulation by using holding company structures. Indeed, holding companies have been used to shift huge amounts of intracompany loans onto the books of German affiliates. At the same time, however, only part of these observed reorganizations seem to have been a reaction to TCR.
Keywords: H25; G38; 330; Multinational firm; debt; thin capitalization; financial structure; Kapitalstruktur; Körperschaftsteuerrecht; Multinationales Unternehmen; Gewinnverlagerung; Deutschland